The early apoptotic DNA fragmentation targets a small number of specific open chromatin regions. - Miriam Di Filippo (Public Library of Science (PLoS), 2009)
We report here that early apoptotic DNA fragmentation, as obtained by using an entirely new approach, is the result of an attack at a small number of specific open chromatin regions of interphase nuclei. This was demonstrated as follows: (i) chicken liver was excised and kept in sterile tubes for 1 to 3 hours at 37 degrees C; (ii) this induced apoptosis (possibly because of oxygen deprivation), as shown by the electrophoretic nucleosomal ladder produced by DNA preparations; (iii) low molecular-weight DNA fragments (approximately 200 bp) were cloned, sequenced, and shown to derive predominantly from genes and surrounding 100 kb regions; (iv) a few hundred cuts were produced, very often involving the same chromosomal sites; (v) at comparable DNA degradation levels, micrococcal nuclease (MNase) also showed a general preference for genes and surrounding regions, but MNase cuts were located at sites that were quite distinct from, and less specific than, those cut by apoptosis. In conclusion, the approach presented here, which is the mildest and least intrusive approach, identifies a preferred accessibility landscape in interphase chromatin.